PENGARUH LATIHAN VARIASI KNEE TUCK JUMP TERHADAP PENINGKATAN TINGGI LONCATAN PADA PESERTA DIDIK EKSTRAKURIKULER BOLA VOLI PUTRA SEKOLAH VOKASI UNGGULAN KOTA BENGKULU - Ilahi, Bogy Restu; Rizky, Oddie Barnanda; Permana, Muhammad Aziez; Nuryogatama, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
Student sports achievements in schools they are affected by factors such as physical condition., technical skills, and training programs. Male volleyball athletes in the extracurricular program at Bengkulu City Vocational School face a significant challenge: low jump height, which affects their ability to perform smash and block techniques effectively. This issue is linked to insufficient specialized training, weak explosive power in leg muscles, and a lack of motivation during practice. The objective of this research is to assess the impact of knee tuck jump variation training on jump height among these athletes. The research employs an experimental method with a one-group pre-test and post-test design. From a population of 30 athletes, 23 were selected through purposive sampling. The vertical jump test was used as the primary instrument, and hypothesis testing was conducted for data analysis.Results show a significant improvement in jump height following the training. The calculated t-value (27.371) exceeded the critical t-value (1.712) at a significance level of α = 0.05, with a 19.47% increase in jump height. These findings confirm the hypothesis, indicating that knee tuck jump variation training effectively enhances jump height among the athletes.